POLA KOMUNIKASI DALAM PEMBELAJARAN AKHLAK STUDI KASUS ASRAMA AL-HIKMAH PP DARUSSALAM BLOKAGUNG - Hasyim Iskandar; Fahris Fahris (JDARISCOMB:Jurnal Komunikasi dan Penyiaran Islam, 2022)
Good communication is a central aspect in the learning and teaching process. This article aims to highlight how the communication pattern in moral learning in the Al-Hikmah dormitory is. Moral learning itself is basically the formation of the character of students. The results showed that the communication pattern of moral learning used was the book TALIMUL MUTAALIM as the medium, and applied the direct learning communication pattern, namely between teachers and students and the indirect learning communication pattern, namely coordination between the teacher and the dormitory administrator.